Gain Enhancement For Whole Ultra-Wideband Frequencies Of A Microstrip Patch Antenna - Abdullah Al-Gburi, Ahmed Jamal; Mohd Ibrahim, Imran; Zakaria, Zahriladha (American Scientific Publishers, 2020)
A rectangular microstrip patch antenna over ultra-wideband with superstrate are designed and analyzed. Four iterations A, B, C, D were designs. Iterations A and B represent the parametric study of the microstrip patch antenna. Iteration C represents Ultrawide band microstrip patch antenna with peak realized gain 4.196 dB at frequency 10.12 GHz, the gain was enhance using superstrate above the microstrip patch antenna as in iteration D, a novel enhancement happens for the whole ultra-wideband frequency band (3.1-10.6 GHz) with highest salient realised gain of 5.3 dB at frequency 10.55 GHz. The proposed antenna gain at iteration D is increased by 26.49%, which is useful for many applications such as satellite communication. Simulation and discussion results of the proposed antenna are present within this paper.